New Guideline for Chronic Kidney Disease 2024, What Primary Care Can Do About It?: A Narrative Review - Simanjuntak, Arya Marganda; Heryadi, Samantha Yaffa; Sembiring, Ligat Pribadi (Indonesian Journal of Kidney and Hypertension, 2026)
Chronic Kidney Disease (CKD) presents an urgent global public health crisis, affecting over 850 million people worldwide, with low-income nations like Indonesia facing a high burden of undiagnosed cases due to limited awareness and a deficient primary care system. This paper serves as a vital, practical response to the novelty of the KDIGO 2024 Clinical Practice Guideline update, which incorporates a decade of new evidence, including the ethical imperative to eliminate the race coefficient from eGFR equations and the introduction of consensus-based "Practice Points." Key findings from this review highlight that CKD diagnosis is not solely reliant on Glomerular Filtration Rate (GFR), but also on persistent markers of kidney damage such as albuminuria and urine sediment abnormalities. The 2024 updates strongly recommend the race-free CKD-EPI 2021 equation for routine screening, the use of estimated GFR based on creatinine and cystatin C (eGFRcr-cys) for superior accuracy, and the strong recommendation for Sodium-Glucose Cotransporter-2 Inhibitors (SGLT2i) in Type 2 Diabetes patients with CKD. Additionally, the guidelines introduce actionable risk prediction thresholds for nephrology referral, alongside practical advice like "sick day rules" for primary care. This review addresses the critical research gap concerning the primary care sector's capacity and capability by synthesizing the KDIGO 2024 updates. It concludes that primary care, as the frontline in health services, must rapidly adopt these standards to enhance early screening, improve patient risk stratification, and facilitate timely, informed referrals to advanced care, thereby mitigating disease progression and improving patient outcomes globally.